Project-based learning assisted augmented reality in increasing students’ mathematical understanding of concepts - Axl Ferrari Fatahillah; Ayu Faradillah (Jurnal Elemen, 2023)
The gap in this study uses Augmented Reality media when the learning system takes place. This research aims to determine the effectiveness of the Project-Based Learning (PjBL)—model in increasing mathematical understanding of concepts assisted by Augmented Reality. The method used in this study uses a quantitative methodology with a quasi-experimental research design with a nonequivalent control group design approach. The random cluster sampling technique was used for sampling in this study. The class used was ten science four class as the control class and ten science five class as the experimental class. Validity and reliability test were carried out with the help of Winstep 3.73 software and data analysis techniques using SPSS 24.0 for Windows software. The total question of the instrument is five, which contains indicators of mathematical understanding concepts. The results of this study are that the experimental class using the Augmented Reality-assisted Project Based Learning (PjBL) model is better than the control class using conventional models. The implications of this research are to assist teachers in improving students’ ability to mathematical understanding concepts and improve innovative learning methods in the classroom with the PjBL models and augmented reality.